Effect of hypoxia-inducible factor 1 on vascular endothelial growth factor expression in exercised human skeletal muscle: a systematic review and meta-analysis - Aragón-Vela, Jerónimo; Casuso, Rafael A. (American Journal of Physiology: Cell Physiology, 2025)
This analysis shows that both HIF-1α mRNA and protein levels are significantly elevated in skeletal muscle following dynamic exercise. However, the absence of a clear relationship between HIF-1α mRNA and the mRNA levels of its downstream target VEGF suggests that HIF-1α mRNA expression alone may not reliably reflect its regulatory role in VEGF transcription in response to exercise. Given the limited number of human studies examining posttranslational regulation of HIF-1α, its precise contribution to VEGF-mediated angiogenic signaling in exercised skeletal muscle remains uncertain. Within contracting human skeletal muscle (SKM), oxygen pressure significantly drops, which has been linked to the activation of a signaling cascade mediated by hypoxia-inducible factor 1α (HIF-1α). This cascade leads to SKM angiogenesis through vascular endothelial growth factor (VEGF). However, the role of HIF-1α in exercise-induced VEGF expression within SKM remains unclear. In this study, we systematically reviewed the literature to quantitatively synthesize all available evidence on HIF-1α activation in exercised human muscle. We identified 21 studies providing 39 effect sizes of pre- and postexercise SKM HIF-1α data from 235 subjects, with 15 of them also presenting data on VEGF mRNA levels. HIF-1α mRNA increased in response to high-intensity and resistance exercise, regardless of participants’ physical fitness levels. Notably, meta-regression showed that exercise-induced VEGF expression is not modulated by HIF-1α mRNA levels. Similarly, when plotting exercise-induced fold changes of VEGF and HIF-1α, no significant relationship was observed. Our findings demonstrate that HIF-1α is expressed in contracting SKM. However, the role of HIF-1α in the exercise-induced angiogenic response remains unclear, as most of the available evidence is limited to transcriptional data. NEW & NOTEWORTHY This analysis shows that both HIF-1α mRNA and protein levels are significantly elevated in skeletal muscle following dynamic exercise. However, the absence of a clear relationship between HIF-1α mRNA and the mRNA levels of its downstream target VEGF suggests that HIF-1α mRNA expression alone may not reliably reflect its regulatory role in VEGF transcription in response to exercise. Given the limited number of human studies examining posttranslational regulation of HIF-1α, its precise contribution to VEGF-mediated angiogenic signaling in exercised skeletal muscle remains uncertain.